2010
DOI: 10.1038/ki.2010.38
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors contribute to the depressive affect among African Americans with chronic kidney disease

Abstract: Depression is common in end-stage renal disease and is associated with poor quality of life and higher mortality; however, little is known about depressive affect in earlier stages of chronic kidney disease. To measure this in a risk group burdened with hypertension and kidney disease, we conducted a cross-sectional analysis of individuals at enrollment in the African American Study of Kidney Disease and Hypertension Cohort Study. Depressive affect was assessed by the Beck Depression Inventory II and quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 48 publications
(113 reference statements)
6
69
2
2
Order By: Relevance
“…Our findings suggest that mental health is a stronger outcome predictor in AA MHD patients. Our findings of poor mental health score and poor clinical outcomes in AA MHD patients are consistent with a report of Fischer et al (62), who found, among a cohort of 628 AAs with stages 3 to 5 CKD, a high prevalence of increased depressive affect that was infrequently treated with anti-depressants and that was associated with poorer quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings suggest that mental health is a stronger outcome predictor in AA MHD patients. Our findings of poor mental health score and poor clinical outcomes in AA MHD patients are consistent with a report of Fischer et al (62), who found, among a cohort of 628 AAs with stages 3 to 5 CKD, a high prevalence of increased depressive affect that was infrequently treated with anti-depressants and that was associated with poorer quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Being female was significantly associated with depression. The finding is similar with the study conducted in USA [16]. Findings from different studies showed that depression is common in females.…”
Section: Socio-economic and Demographic Characteristicssupporting
confidence: 90%
“…19 Similarly, the prevalence of at least moderate depressive symptoms was 26% among subjects with hypertensive CKD in the African-American Study of Kidney Disease and Hypertension Cohort Study. 20 The Cardiovascular Health Study found that in their community-based cohort of elderly subjects, those with depressive symptoms had 19% greater odds of impaired eGFR (95% CI=1.01-1.40) compared to those without, after adjustment for demographics, clinical variables, and health behaviors.…”
Section: Depression and Anxiety And Rrt Modalitiesmentioning
confidence: 99%